Study on the transformation of diamond into graphene through high-temperature annealing - Li, Xiaogang; Zhang, Xueyu; Ren, Ying; Wöhrl, Nicolas; Lv, Wei; Wang, Honglin; Li, Zhengxin (Ceramics international, 2025)
The carbon allotropes, diamond and graphene, possess distinctly properties that can be effectively harnessed by combining them into a graphene-diamond composite structure. However, the growth mechanisms of graphene or solid carbon source graphite from surface graphitization of diamond remains poorly understood. In this study, the graphene growth directly out of polycrystalline diamond by employing high-temperature annealing with Cu as a catalyst. After annealing at 1100 °C for 15–30 min, the resulting surface film layer exhibited typical features of graphene in Raman spectra. I2D/IG values of 0.61 and 0.63 were observed, respectively, indicating that a graphene layer count exceeding four. Furthermore, the parallel growth of graphene on diamond surface was successfully observed using TEM. Reconstruction of two different types of graphene-diamond composite structures, constructed from lamellar and sp3 and sp2 bonds, is comprehensively elucidated. These structures are expected to synergistically combine the ultra-hard characteristics of diamond with the high fracture toughness and ductility of graphene.